How values of individualism and collectivism influence impulsive buying and money budgeting: the mediating role of acculturation to global consumer culture. Issue 5 (29th June 2020) - Czarnecka, Barbara; Schivinski, Bruno; Keles, Serap
Abstract: This study examined the effects of individual‐level cultural values of individualism and collectivism on impulsive buying and money budgeting and the mediating role of acculturation to global consumer culture. By applying the person‐environment fit theory and acculturation theory, we argue that people who hold cultural values congruent with the culture they come into contact with are more likely to acculturate to it, and that those who acculturate to global consumer culture (GCC) are more likely to display consumption behaviors stimulated by GCC, namely impulsive buying and poor money budgeting. The findings show that consumers acculturated to GCC report higher impulsive buying and lower money budgeting, and that it is not the distinction between individualism and collectivism, but rather between the vertical and horizontal values that determines the acceptance of GCC and the studied consumption behaviors. Results revealed that vertical individualists (those who believe in competition between individuals and who prioritize their needs over the needs of others) and vertical collectivists (those who believe in the subordination of individuals to groups) were more likely to be acculturated to GCC. Thus, the acceptance of inequality between individuals among other individuals, or within groups, is related to the acceptance of GCC and impulsive buying and money budgeting. The level of acculturation to GCC mediates the relations between vertical individualism and collectivism values and impulsive buying and money budgeting. Theoretical contributions to the research on horizontal/vertical individualism/collectivism, acculturation to GCC, and person‐environment fit theory, as well as practical implications for marketers are discussed.